Relação peso-comprimento e comprimento-comprimento, para espécies de peixe do baixo rio Araguaia, cerrado brasileiro - França, Fellipe Manoel de Sousa (2023)
The relationships between weight-length (LWR) and length-length (LLR) are essential tools for ichthyofauna management and monitoring programs. Were analyzed the relationships for length-weight (LWR) and length-length (LLR) of 51 fish species captured in the lower Araguaia River region in the Brazilian Cerrado. All LWR adjustments were significant, with b values ranging from 2.01 to 3.50. Most of the species exhibited isometric growth. All LLR results indicated highly correlated coefficient of determination (r²) values, all exceeding 0.75, except for one species. According to the FishBase database, unprecedented sizes for the maximum length were recorded for 23 species, as well as maximum weight for eight species. Finally, the information presented in this study regarding the relationship between weight and length of the ichthyofauna in the lower Araguaia River environment, along with other biological data for these species, may assist the development of strategies for conservation and monitoring.